2010
DOI: 10.15369/sujms.22.127
|View full text |Cite
|
Sign up to set email alerts
|

Three Cases of Noninvasive Carcinoma ex Pleomorphic Adenoma of the Parotid Gland and a Literature Survey Focusing on their Clinicopathologic Features

Abstract: IntroductionOnly 30 cases of non-invasive intra-capsular carcinoma ex pleomorphic adenoma have been reported in the English language literature [1][2][3][4][5] . Here, we report three cases of noninvasive carcinoma ex pleomorphic adenoma and we have carried out a literature survey. Table 1-1, 1-2 Case Reports Case 1A 61-year-old man was admitted to hospital, presenting with a mass in the parotid gland. The prognosis and therapeutic appoach will depend on evidence of capsular invasion. HER-2/neu is a useful ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…In a review of thirty cases and a report of an additional three cases, only one case showed recurrence or metastasis. 3 This favorable outcome certainly contrasts with that of the widely invasive type where metastasis is reported to occur in up to 70% of cases. 1 Another review of ten cases showed one case developing metastasis, and recommended that non-invasive cases should thus still be followed up closely after primary treatment because regional or distant metastasis can occur.…”
mentioning
confidence: 93%
See 1 more Smart Citation
“…In a review of thirty cases and a report of an additional three cases, only one case showed recurrence or metastasis. 3 This favorable outcome certainly contrasts with that of the widely invasive type where metastasis is reported to occur in up to 70% of cases. 1 Another review of ten cases showed one case developing metastasis, and recommended that non-invasive cases should thus still be followed up closely after primary treatment because regional or distant metastasis can occur.…”
mentioning
confidence: 93%
“…By morphologic sub-type the most commonly reported carcinoma arising in a pleomorphic adenoma is a salivary duct carcinoma or an adenocarcinoma that is not otherwise specified (NOS). 1,3 Residual pleomorphic adenoma tissue is identifiable either in its typical morphology, a chondromyxoid stroma, or a hyalinized sclerotic nodule. 1 Aside from the type of carcinoma arising from the pleomorphic adenoma, another parameter that has to be reported is the extent of involvement by the carcinomatous component.…”
mentioning
confidence: 99%